Effects of Fennel Supplementation on Biochemical Blood Indices in Females During Climacteric Period – Preliminary Reports - Karina Kwiatkowska; Aneta Teległów; Szymon Podsiadło; Olga Czerwińska-Ledwig; Agnieszka Suder (Rehabilitacja Medyczna)
Introduction: The menopausal period in women, also called climacteric, is the time when several hormonal changes take place and gonadal functions disappears. Although medicinal such as Fennel plants (Foeniculum vulgare Mill.) feature a relatively weaker effect than synthetic drugs, they are more commonly applied in different societies or ethnical groups due to the lower probability of side effect occurrence during the climacteric period in females.Objectives: The aim of the work was to assess blood biochemical indices in menopausal women and quality of life after fennel supplementation.Materials and methods: The research included 10 females aged 43-69 years with observed climacteric symptoms. Blood was taken twice (before fennel seed supplementation and after it) on an empty stomach, in the morning. Selected biochemical blood indices were tested in all the participants.Results: Comparing the examined group results before and after fennel supplementation, statistically significant changes were found for the following indices: HCT [%], MCV [fl], MCHC [g/dl], CHCM [g/dl], HDW [g/dl] and Basophils [%]. No changes were observed for: RBC [1012/l], HGB [g/dl], MCH [pg], RDW [%], WBC [109/l], neutrophils [%], lymphocytes [%], monocytes [%], eosinophils [%], LUC [%], neutrophils [109/l], lymphocytes [109/l], monocytes [109/l], eosinophils [109/l], basophils [109/l], LUC [109/l], PLT [109/l], MPV [fl], PCT [%], PDW [%], iron [umol/l], ASPAT [U/l], ALAT [U/l], total cholesterol [mmol/l], cholesterol HDL [mmol/l], cholesterol LDL [mmol/l], urea [mmol/l], creatinine [umol/l], eGFR [ml/min/1,732], alpha-Amylase [U/l] or Lipase [U/l].Conclusions: Fennel (Foeniculum vulgare Mill.) favours women’s health and may eliminate unbearable climacteric symptoms. Our research confirmed the occurrence of differences in blood morphology test results in females after fennel supplementation in relation to the results of tests performed before it.